2011
DOI: 10.5423/ppj.2011.27.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Attenuation of Pectobacterium carotovorum Using N-Acyl-homoserine Lactone Degrading Bacteria Isolated from Potato Rhizosphere

Abstract: Several soil bacteria were found to degrade N-Acylhomoserine lactones (NAHLs), thereby interfering with the bacterial quorum sensing system. In this research, fifteen strains of NAHL degrading rhizobacteria were isolated from potato rhizosphere. Based on phenotypic characteristics and 16S rDNA sequence analyses, the strains were identified as members of genera Bacillus, Streptomyces, Arthrobacter, Pseudomonas and Mesorhizobium. All tested isolates were capable to degrade both synthetic and natural NAHL produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…In addition to direct toxic effects on other microbes, nitrous oxide production by Streptomyces has been suggested to activate plant defenses, improving the plant's protection against pathogens (597). Recently, Mahmoudi et al (559) reported that streptomycetes can degrade the signaling compounds that coordinate the expression of genes required for pathogenicity in Pectobacterium carotovorum, suggesting a further mechanism for disease suppression. In addition, the production of chitinases or plant growth-promoting compounds has been reported to contribute to disease suppression by some Streptomyces isolates (598)(599)(600)(601).…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to direct toxic effects on other microbes, nitrous oxide production by Streptomyces has been suggested to activate plant defenses, improving the plant's protection against pathogens (597). Recently, Mahmoudi et al (559) reported that streptomycetes can degrade the signaling compounds that coordinate the expression of genes required for pathogenicity in Pectobacterium carotovorum, suggesting a further mechanism for disease suppression. In addition, the production of chitinases or plant growth-promoting compounds has been reported to contribute to disease suppression by some Streptomyces isolates (598)(599)(600)(601).…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
“…The Actinobacteria are widely recognized for their potential in biocontrol (553-555) because they are important producers of bioactive compounds (556). Over the past 50 years, there have been many studies on the mechanisms by which Actinobacteria might inhibit pathogens in soil, including antibiosis, nutrient competition, production of degradative enzymes, nitrous oxide production, and quorum quenching (557)(558)(559). Their adaptability to different environments in the rhizosphere makes them a strong competitor.…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
“…carotovorum (1×10 6 CFU/ ml) and 15 μl plant extract (Dill extract) 15 . Agria) were washed with tap water, surface-sterilized with sodium hypochlorite (5 %) and were then rinsed using sterile water after air-drying under sterile conditions.…”
Section: Bioassays For Attenuation Of Plant Soft Rot Test On Potato Tmentioning
confidence: 99%
“…However, the major traits of Actinobacteria are the production of a wide variety of bioactive compounds [108] and many well-known mechanisms by which they inhibit plant pathogens in the soil. Some of these mechanisms include antibiosis, nutrient competition, quorum quenching, and production of degradative enzymes and nitrous oxide [109,110].…”
Section: Pgp Streptomyces Against Biotic Stressorsmentioning
confidence: 99%